(untitled) (Proceedings of International Conference on Special Education, 2019)
This research is based on the problem of lack of deaf children’s ability in an expressive language. Research aims to develop the expressive language skills of deaf children and target child behavior in expressing desire. The subject of this research is the deaf student at SKh Bina Citra Anak. The method used is Single Subject Research with A-B-A research design. The developments can be seen in phase A1, phase B and phase A2. The processed Data is presented in a simple descriptive statistical form through graphs and percentage values. The results showed a significant development on the expressive language of the research subject using Pico Card media with the evidence of the acquisition of the mean phase A1 level of 57% to 79% at the mean phase level A2. Then the use of Pico Card Media is effective in enhancing the expressive language ability of deaf children